Error Analysis on Classroom Language Made by Pre-service Teachers of English Education Program UNP - Mir-atul Aufa; Hermawati Syarif (Universitas Negeri Padang, 2020)
This study aimed to analyse the errors on pre-service teachers’ classroom language while having field practice in senior high schools. The analysis was conducted by adapting James (1998) Target Modification Taxonomy. Classroom language including the simple instructions and the questions given by pre-service teachers. The participants of this research are five pre-service teachers from four different schools. This study was descriptive qualitative research. The instrumentation of this research were observation, document and interview. The study analyzed pre-service teachers’ classroom language by categorizing the errors into types followed by the causes of each error. Some problems related to pre-service teachers’ classroom language were also found. The problems found hindered the optimal use of classroom language. The findings of the research showed that there were grammatical and lexical errors occured. The grammatical errors were omission (50%), overinclusion (21.73%), misselection (8.70%) and misplacement (4.34%). Some ellipsis (15.21%) were also detected.